2003
DOI: 10.1074/jbc.m300841200
|View full text |Cite
|
Sign up to set email alerts
|

A Specific Domain of Giα Required for the Transactivation of Giα by Tubulin Is Implicated in the Organization of Cellular Microtubules

Abstract: ␣ subunits bind tubulin with high affinity, whereas transducin (G t ␣) does not. The interaction between tubulin and G␣, which also involves the direct transfer of GTP from tubulin to G␣ (transactivation), is not yet fully understood. This study, using chimeras of G i ␣ and G t ␣, showed that the G i ␣ (215-295) segment converted G t ␣ to bind to tubulin and this chimera (chimera 1) could be transactivated by tubulin. Insertion of G t ␣ (237-270) into chimera 1 to form chimera 2 resulted in a protein that, lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 32 publications
1
29
0
Order By: Relevance
“…Yeast two-hybrid 1 to 1 interaction assays of GIV with G␣ family members. GIV interacts with G␣ i1, G␣ 2, G␣ 3, G␣ 0, G␣ z , G s , and the yeast G␣ i homolog GPA1, but it does not interact with G␣ q , G␣ 12 , and G␣ 13 and reacts very weakly with the activated mutant, G␣ s (Q226L). Interactions were analyzed qualitatively by a colony lift assay on three independent clones using 5-bromo-4-chloro-3-indolyl D-galactoside (14), and the appearance of blue colonies was assessed after 2, 4, and 8 h. No background color was detected after 20 h.…”
Section: Giv Interacts With the G␣ I And G␣ S Subfamilies Of G Proteins-mentioning
confidence: 99%
“…Yeast two-hybrid 1 to 1 interaction assays of GIV with G␣ family members. GIV interacts with G␣ i1, G␣ 2, G␣ 3, G␣ 0, G␣ z , G s , and the yeast G␣ i homolog GPA1, but it does not interact with G␣ q , G␣ 12 , and G␣ 13 and reacts very weakly with the activated mutant, G␣ s (Q226L). Interactions were analyzed qualitatively by a colony lift assay on three independent clones using 5-bromo-4-chloro-3-indolyl D-galactoside (14), and the appearance of blue colonies was assessed after 2, 4, and 8 h. No background color was detected after 20 h.…”
Section: Giv Interacts With the G␣ I And G␣ S Subfamilies Of G Proteins-mentioning
confidence: 99%
“…The full-length constitutively active mutant Q227L G s protein ␣ subunit plasmid was a gift from Dr. Tohru Kozasa (University of Illinois at Chicago). The plasmid encoding NC1 (chimera 3) protein has been described previously (23).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, we observed that expression of a dominant-negative G␣ i -transducin chimera (NC1) that blocks G␣ s binding to tubulin and G␣ s activation of tubulin GTPase, attenuating microtubule-based cellular projections in COS-1 cells (23). Here NC1 was used to determine the role of G␣ s in neurite outgrowth (Fig.…”
Section: A Dominant-negative Protein That Blocks Tubulin Association mentioning
confidence: 99%
“…Specifically, the ␣3-␤5 loop of G␣ s was replaced with homologous residues from G␣ t . A similar approach has been used successfully to dissect the interface of G␣ subunits with other proteins, including tubulin (13,16,27,28).…”
Section: G␣ S Activation Of Tubulin Gtpase Is Unaltered By Mutating Tmentioning
confidence: 99%
“…To further understand the role of these regions in binding, 15-amino acid-long peptides cor- responding to the ␣3-␤5 regions (P3) or residues 28 -42 (peptide N) were synthesized (supplemental Table 2). Control peptides (peptides G t N and G t 3) were derived from G␣ t , which does not bind tubulin (11,27), and corresponded to homologous regions on G␣ s . The affinities of all peptides for tubulin were determined.…”
Section: Binding and Kinetics Of G␣ S -Tubulin Complexes-func-mentioning
confidence: 99%